Contribution à l’étude de la filière « Kasu » Tetracarpidium conophorum (Mull.Arg) Hutch & Dalz (Euphorbiaceae) : un des produits forestiers non ligneux de Kisangani et ses environs (R.D. Congo) - Gambi, Ghislaine Katuala; Benjamin Bembonga Moganga; Jean-Pierre Mate Mweru (IJRDO - Journal of Business Management, 2021)
The increase of the demand in seed of the false cashew nut in the city of Kisangani, the lack of information and the suitable research deficiency on this liana motivated our obstruction to lead this survey. This last has been led in 5 villages situated between 72 and 85 km of the city of Kisangani, on the axis road Kisangani-Opala where is exploited this resource, and in the city of Kisangani where she/it is marketed. The main objective of this survey consisted in determining the socio-economic potentialities of Tetracarpidium conophorum within the riparian population situated on aforesaid road axis. Accelerated method of research by participating scheduling and the systemic approach is the tools that allowed us to interview 650 actors of the chain. Being about the exploitation of the resource, the techniques of harvest counted are slaughtering (5,28%), the pickup (20,82%) and the picking (73,90%). The investigatings led by the different sellers show that the earnings generated for a campaign of activities of 6 months (of June to November) vary between 360 000 – 1 728 000CDF for the wholesalers and 2 760 000 - 4 140 000CDF for the retailers. The consumption of the seeds is either daily, either weekly and vary according to the surroundings. The led investigations also show that is exploited also for its leaves, its peels and its roots this NWFP, in addition to the seeds, that them, enter in the traditional pharmacopeia. The results contained in this work constitute a tool of help to the decision for the management rational and lasting of this forest resource. We propose that the research for this liana continue also on the ecological aspects for his best management.